Silicon/nitrogen synergistically reinforced flame-retardant PA6 nanocomposites with simultaneously improved anti-dripping and mechanical properties. Issue 14 (6th March 2019) - Fan, Shuo; Yuan, Ruchao; Wu, Dequn; Wang, Xueli; Yu, Jianyong; Li, Faxue
Abstract : A facile route was provided to prepare silicon/nitrogen synergistically reinforced flame-retardant PA6 nanocomposites with simultaneously improved anti-dripping and mechanical properties. Abstract : A facile route of 'copolymerization/blending' was proposed to fabricate silicon/nitrogen synergistically reinforced flame-retardant PA6 nanocomposites with simultaneously improved anti-dripping and mechanical properties. Firstly, a persistently inherent flame-retardant PA6 (FR-PA6), with 1, 3-bis(3-aminopropyl)tetramethyl disiloxane (MSDS), was synthesized via controllable amidation and a polycondensation reaction. Melamine cyanurate (MCA) nanoparticles as a 'gas phase' synergistic agent were then added into FR-PA6 to further improve its flame retardancy. The primarily obtained FR-PA6 could be extinguished after a few melt droplets dropped as ignited, and passed the V-2 rating with enhanced mechanical properties, while PA6 had no rating (NR). The prepared FR-PA6/MCA nanocomposites could attain a limiting oxygen index (LOI) value of 32.7%, and passed the V-0 level with only 1 melting droplet with similar mechanical properties to PA6. Accordingly, the special 'condensed-gas phase' synergistic flame-retardant mechanism of FR-PA6/MCA nanocomposites was proposed through studying the residues and pyrolysis volatiles. This work provided a facile route as a model for developing functional PA6 for diverse engineering applications.